KELUHAN DENGAN KEPUASAN PASIEN RAWAT JALAN JAMINAN KESEHATAN NASIONAL DI RUMAH SAKIT LUDIRA HUSADA TAMA - Tedy Candra Lesmana; Norwakiah Norwakiah (LLDIKTI Wilayah X, 2021)
The A-level reference in the National Health Insurance System (JKN) causes hospital outpatient to increase and can lower the quality of health services. Ludira Husada Tama Hospital for 2 years (2017-2018) received an outpatient complaint to the service provided. This research is to know the relationship of complaints and the satisfaction of an outpatient in Ludira Husada Tama Hospital. The research used is quantitative with a cross sectional approach. Samples of 97 of the 3,692 patients with JKN participants were taken with accidental sampling. Complaints and satisfaction Data are collected with questionnaires. The relationship between complaints and satisfaction is analyzed with Fisher test. It is known that 18.6% of patients complain on health services provided, while 81.4% are not. A total of 57.7% of patients were satisfied with health care, while 42.3% did not. There is a relationship between service complaints and patient satisfaction. Hospitals are expected to conduct regular evaluation of the services provided. Efforts to improve patient satisfaction can be done by improving the comfort of the waiting room and arranging the re-scheduling of the doctor's hours